2022
DOI: 10.3389/fcvm.2022.860600
|View full text |Cite
|
Sign up to set email alerts
|

How Parental Predictors Jointly Affect the Risk of Offspring Congenital Heart Disease: A Nationwide Multicenter Study Based on the China Birth Cohort

Abstract: ObjectiveCongenital heart disease (CHD) is complex in its etiology. Its genetic causes have been investigated, whereas the non-genetic factor related studies are still limited. We aimed to identify dominant parental predictors and develop a predictive model and nomogram for the risk of offspring CHD.MethodsThis was a retrospective study from November 2017 to December 2021 covering 44,578 participants, of which those from 4 hospitals in eastern China were assigned to the development cohort and those from 5 hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The CBCS was conducted in 38 research centres in China. 15 The quality control measures on data homogeneity are essential in a multicentre cohort study. The study cohort, followed-up strategies, data collection and data management can be found in the published paper.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…The CBCS was conducted in 38 research centres in China. 15 The quality control measures on data homogeneity are essential in a multicentre cohort study. The study cohort, followed-up strategies, data collection and data management can be found in the published paper.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…Unfortunately, we only obtained information on the presence or absence of CHD in offspring without the specific subtypes. Still, concerning a published article using data from the CBCS, 15 the three most common types were ventricular septal defect, multiple CHD and tetralogy of Fallot.…”
Section: Data Collection and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation